Digital 3D Animation of Powder-Snow Avalanches - Nascimento, Filipe; Paiva, Afonso (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI); 2025: Anais Estendidos da XXXVIII Conference on Graphics, Patterns and Images, 2025)
Physically based animation of fluids such as smoke, water, and fire provides some of the most stunning computer graphics in the entertainment industry. However, several phenomena still need to be fully understood, and their formulations are still the focus of intense research in other fields, such as Physics and Civil Engineering. That is the case with snow avalanches, whose numerical modeling is challenging due to their complex dynamics. The manipulation of such phenomena is new to computer graphics, and few works exist. This project aims to bring these formulations to the field of computer graphics regarding the digital animation of powder-snow avalanches.